A Genetic Linkage Map for Cattle - Bishop, M. D. (1994)
We report the most extensive physically anchored linkage map for cattle produced to date. Three-hundred thirteen genetic markers ordered in 30 linkage groups, anchored to 24 autosomal chromosomes (n = 29), the X and Y chromosomes, four unanchored syntenic groups and two unassigned linkage groups spanning 2464 cM of the bovine genome are summarized. The map also assigns 19 type I loci to specific chromosomes and/or syntenic groups and four cosmid clones containing informative microsatellites to chromosomes 13, 25 and 29 anchoring syntenic groups U11, U7 and U8, respectively. This map provides the skeletal framework prerequisite to development of a comprehensive genetic map for cattle and analysis of economic trait loci (ETL).